2021
DOI: 10.1002/gps.5655
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among older adults: Findings from the ELSI‐Brazil study

Abstract: Objectives This study estimates the national prevalence of drinking patterns (current, heavy, and binge) and the associated factors, among older Brazilians. Design Cross‐sectional study using survey data from ELSI‐Brazil (2015–2016). Setting/Participants A total of 7839 adults aged 50 years or older. Measurements Respondents were asked about alcohol drinking. Alcohol consumption status was categorized as current drinkers (last month), heavy drinkers (≥7 drinks/week for females and ≥14 drinks/week for males), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…The present findings are partially in line with a recent report pooling data from eight Finnish cohorts, 24 which found negative mediated interactive effects of alcohol intake on the association between income and alcohol‐attributable mortality. Interestingly, a negative proportion for differential exposure was noted in this study, and such a divergence from the present findings could be attributed—besides the fact that the outcomes are distinct—to different societal vulnerability factors and drinking patterns when comparing Finland and Brazil 42–44 . Another study detected a minimal attenuation in the effects of socioeconomic inequalities in alcohol‐related disorders after adjusting for the amount of alcohol use, using traditional mediation analysis in a Swedish cohort 26 .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The present findings are partially in line with a recent report pooling data from eight Finnish cohorts, 24 which found negative mediated interactive effects of alcohol intake on the association between income and alcohol‐attributable mortality. Interestingly, a negative proportion for differential exposure was noted in this study, and such a divergence from the present findings could be attributed—besides the fact that the outcomes are distinct—to different societal vulnerability factors and drinking patterns when comparing Finland and Brazil 42–44 . Another study detected a minimal attenuation in the effects of socioeconomic inequalities in alcohol‐related disorders after adjusting for the amount of alcohol use, using traditional mediation analysis in a Swedish cohort 26 .…”
Section: Discussioncontrasting
confidence: 95%
“…Interestingly, a negative proportion for differential exposure was noted in this study, and such a divergence from the present findings could be attributedbesides the fact that the outcomes are distinct-to different societal vulnerability factors and drinking patterns when comparing Finland and Brazil. [42][43][44] Another study detected a minimal attenuation in the effects of socioeconomic inequalities in alcohol-related disorders after adjusting for the amount of alcohol use, using traditional mediation analysis in a Swedish cohort. 26 In some sort, this finding is equivalent to a negative total indirect effect, similar to what we found, although we were able to disentangle the contribution of each component of the mediated and interactive effects.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…These sex differences associated with alcohol intake can largely be attributed to differences in alcohol consumption between men and women. A study investigating the national prevalence of drinking patterns among Brazilians aged 55 years or older showed that heavy drinking and binge drinking are more prevalent in males, and are associated with higher education and younger age [30] In our study, men consumed greater quantities of alcohol in grams per week than women in all groups. In addition, in the analysis of the sample loss, the highest percentage of participants who died between evaluations were men who had higher alcohol consumption than the remaining sample.…”
Section: Discussionmentioning
confidence: 58%
“…The total number of chronic conditions was estimated from self‐report of 14 conditions (hypertension, diabetes, high cholesterol, myocardial infarction, angina, heart failure, stroke, asthma, chronic obstructive pulmonary disease, arthritis, osteoporosis, chronic back pain, cancer, and chronic kidney disease). In men, drinking 14 or more doses a week, or 5 or more a day, was classified as “problematic alcohol drinking”; among women, this referred to drinking 7 or more doses a week, or 4 or more a day 32,33 …”
Section: Methodsmentioning
confidence: 99%
“…In men, drinking 14 or more doses a week, or 5 or more a day, was classified as "problematic alcohol drinking"; among women, this referred to drinking 7 or more doses a week, or 4 or more a day. 32,33 These variables were chosen as covariates (potential confounders) as they are more likely to be simultaneously associated with hearing loss and cognitive impairment or depressive symptoms.…”
Section: Other Variablesmentioning
confidence: 99%